Polymer Composite Containing Carbon Nanotubes and their Applications - Park, Sung-Hoon; Bae, Joonwon (Recent Patents on Nanotechnology, 2017)
Background: Carbon nanotubes (CNTs) are attractive nanostructures in this regard, primarily due to their high aspect ratio coupled with high thermal and electrical conductivities. Consequently, CNT polymer composites have been extensively investigated for various applications, owing to their light weight and processibility. However, there have been several issues affecting the utilization of CNTs, such as aggregation (bundling) which leads to a non-uniform dispersion and poor interfacial bonding of the CNTs with the polymer, resulting in variation in composite performance, along with the additional issue of high cost of CNTs. Description: In this article, recent research and patents for polymer composites containing carbon nanomaterial are presented and summarized. In addition, a rationale for optimally designed carbon nanotube polymer composites and their applications are suggested. Above the electrical percolation threshold, a transition from insulator to conductor occurs. The percolation threshold values of CNT composite are dependent on filler shape, intrinsic properties of filler, type of polymer, CNT dispersion condition and so on. Different values of percolation threshold CNT polymer composites have been summarized. The difference in percolation threshold and conductivity of CNT composites could be explained by the degree of effective interactions between nanotubes and polymer matrix. The reaction between surface functional groups of CNTs and polymer could contribute to better dispersion of CNTs in polymer matrix. Consequently, it increased the number of electrical networks of CNTs in polymer, resulting in an enhancement of composite conductivity. In addition, to exfoliate nanotubes from heavy bundles, ultrasonication with proper solvent and three roll milling processes were used. Potential reactions of covalent bonding between functionalized CNTs and polymer were suggested based on the above rationale. Conclusion: Through the use of CNT functionalization, high aspect ratio CNTs, and proper fabrication, uniform dispersion of nanotubes in polymer can be achieved leading to considerable improvement in electrical conductivity and electromagnetic interference (EMI) shielding properties.
Keywords: electrical percolation threshold